Functional organization of the ventral occipitotemporal regions for Chinese orthographic processing. (August 2020) - Tian, Mengyu; Li, Hehui; Chu, Mingyuan; Ding, Guosheng
Abstract: Previous studies have found that the orthographic representation of alphabetic languages is hierarchically organized from the posterior to the anterior parts of the left ventral occipitotemporal area (vOT). More word-like stimuli, such as real words and pseudo-words, induced higher activation in the middle and the anterior parts of the left vOT compared to false fonts or consonant letter strings, while different types of orthographic stimuli induced equal activation in the posterior part of the left vOT. In addition, such hierarchically tuning effect was not found in the right vOT. However, it remains unclear whether such a hierarchical organization can be generalized to the processing of logographic languages, such as Chinese. In the present study, we examined Chinese orthographic processing in the vOT with a passive view task using functional magnetic resonance imaging (fMRI). Similar to alphabetic languages, the posterior part of the vOT responds equivalently to different types of Chinese stimuli, including real characters, pseudo-characters, false characters, and stroke combination, indicating its role in general visual processing. Unlike alphabetic languages, however, we found that false characters induced stronger responses compared to real characters and pseudo-characters in the middle part of the left vOT as well as the middle part of the right vOT. These findings demonstrate that the features of orthographic organization in bilateral vOTs may differ between Chinese and alphabetic languages, suggesting that the functional organization of the vOTs is modulated by different orthographic conventions. Highlights: Neural representation of orthography in Chinese was examined in bilateral vOT. False character induced highest activation in the left vOT. The right vOT showed a similar activation pattern to the left vOT. The findings suggest orthographic convention impacts functional organization of vOT.